2022
DOI: 10.1002/osp4.617
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing a widely available weight loss program with gamified inhibitory control training: A randomized pilot study

Abstract: Background: Increasing evidence suggests that targeting self-regulatory processes may improve obesity treatment outcomes. Incorporating gamification principles in inhibitory control training may promote sustained training adherence and resulting benefits. This pilot study evaluated the preliminary efficacy of supplementing an evidence-based weight management program (WW) with sustained gamified inhibitory control training (PolyRules!) on change in Body Mass Index (BMI) among adults with overweight/obesity. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In this review, some studies (31/70, 44%) indicated that relevant theories or concepts guided their gamification practices in the self-management of patients with chronic diseases. A total of 37 concepts or theoretical frameworks were mentioned in the included articles, most of which originated from psychology and cross-disciplinarity (n=33, 89%), such as self-determination theory [38,40,[42][43][44], flow theory [33,[45][46][47][48][49], social cognition theory [27,[50][51][52], goal-setting theory [34,43], information-motivation-behavioral technology model of behavior change [32,43], intrinsic motivation [16,53], self-efficacy [17,45], persuasion system design model [54], inhibitory control [55,56], patient-reported outcome [32], co-design approach, and participatory design [57].…”
Section: Theoretical Supportmentioning
confidence: 99%
See 3 more Smart Citations
“…In this review, some studies (31/70, 44%) indicated that relevant theories or concepts guided their gamification practices in the self-management of patients with chronic diseases. A total of 37 concepts or theoretical frameworks were mentioned in the included articles, most of which originated from psychology and cross-disciplinarity (n=33, 89%), such as self-determination theory [38,40,[42][43][44], flow theory [33,[45][46][47][48][49], social cognition theory [27,[50][51][52], goal-setting theory [34,43], information-motivation-behavioral technology model of behavior change [32,43], intrinsic motivation [16,53], self-efficacy [17,45], persuasion system design model [54], inhibitory control [55,56], patient-reported outcome [32], co-design approach, and participatory design [57].…”
Section: Theoretical Supportmentioning
confidence: 99%
“…Overall, "human-computer interaction" was an important game design element in the gamification design of the physical activity and rehabilitation training, providing timely feedback data for both health care professionals and patients such as training duration, intensity, and training action; allowing patients to see physical function changes with exercise rehabilitation; and improving their compliance with exercise and rehabilitation [13,16,19,20,28,30,33,35,37,42,44,[46][47][48][49][51][52][53][54][55][56][58][59][60][64][65][66][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83]85].…”
Section: Physical Activity and Rehabilitation Maintainermentioning
confidence: 99%
See 2 more Smart Citations